A Thematic-Holistic Analysis of Post-Divorce Maintenance Obligations and Their Relation to the Supreme Court's SEMA Provisions - Aresanti Kusnia; Izzul Mutho` (al-Afkar, Journal For Islamic Studies, 2026)
Alimony as a crucial obligation of husbands in Islamic family law, reflecting justice, compassion, and responsibility toward wives and children, amid challenges of regulatory ambiguity post-divorce that threaten women's and children's rights due to tensions between Islamic sharia and positive Indonesian law. The primary objective is to analyze the foundations of nafkah in Islamic law, its implementation in national legislation, and mechanisms for protecting rights post-divorce to produce fair and applicable policy recommendations. The methodology adopts a qualitative descriptive approach with a thematic-holistic method, integrating thematic and holistic analysis of Quranic verses and hadiths, synchronized with views from fuqaha of the four madhhabs, the Compilation of Islamic Law (KHI), the Marriage Law, and Supreme Court Circulars (SEMA). The results indicate that the fiqh schools (Maliki, Hanafi, Shafi'i, Hanbali) affirm nafkah encompasses clothing, food, shelter, and other needs for wives, children, and dependents; post-divorce, it focuses on iddah maintenance, mut'ah, and child custody, while Indonesian regulations such as KHI Articles 80 and 149, along with SEMA 2015-2021, strengthen enforcement through annual child maintenance increases of 10-20%, sanctions, and asset seizure guarantees. The thematic-holistic analysis reveals universal values such as shared responsibility and role equality, adaptable to modern contexts. In conclusion, nafkah represents a social responsibility based on maqasid shariah that requires harmonization of sharia, national law, and judicial policy to ensure sustainable fulfillment of post-divorce rights.